A preliminary study on the distribution of morphine and its glucuronides in the subcompartments of bood - Skopp, Gisela; Pötsch, Lucia; Ganßmann, Beate; Aderjan, Rolf; Mattern, Rainer (Journal of analytical toxicology, 1998)
The distribution of morphine, morphine-3-glucuronide (M3G), and morphine-6-glucuronide (M6G) in whole blood, plasma, and packed erythrocytes was studied. Parameters investigated were the hematocrit values (10, 42, 44, and 71%) and the water content of the samples. The blood-to-plasma ratio of morphine concentrations was unaffected by variations in hematocrit and water content, whereas the corresponding ratios for M3G and M6G were strongly influenced. Ratios were 0.53 to 0.65 and 0.52 to 0.62 in specimens with average hematocrit values (42 and 44%, respectively), and the ratios were 0.81 or 0.89 (hematocrit 10%) and 0.27 or 0.28 (hemalocrit 71%) in blood samples with different hematocrit values. In contrast to the morphine conjugates, morphine was highly bound to or partitioned into red blood cells (βe = 55.9). Although the present data are limited, they already demonstrate that conclusions drawn from pharmacokinetic studies and transferred to parent drug to metabolite ratios resulting from forensic blood samples may be biased by the particular biological matrix under investigation.
Gesehen am 15.08.2023